Portal Hypertension and Ascites: Patient-and Population-centered Clinical Practice Guidelines by the Italian Association for the Study of the Liver (AISF). Issue 9 (September 2021) - ,; Bruno, Raffaele; Cammà, Calogero; Caraceni, Paolo; D'Amico, Gennaro; Grattagliano, Ignazio; La Mura, Vincenzo; Riggio, Oliviero; Schepis, Filippo; Senzolo, Marco; Angeli, Paolo; de Franchis, Roberto
Abstract: Portal hypertension and ascites are two crucial events in the natural history of liver cirrhosis, whose appearance marks a downward shift in the prognosis of the disease. Over the years, several international and national societies have issued clinical practice guidelines for the diagnosis and management of portal hypertension and ascites. The present document addresses the needs of an updated guidance on the clinical management of these conditions. Accordingly, the AISF Governing Board appointed a multi-disciplinary committee of experts for drafting an update of the most recent EASL Clinical Practice Guidelines. The aim of this work was to adapt the EASL recommendations to national regulations and resources, local circumstances and settings, infrastructure, and cost/benefit strategies to avoid duplication of efforts and optimize resource utilization. The committee defined the objectives, the key issues and retrieved the relevant evidence by performing a systematic review of the literature. Finally, the committee members (chosen on the basis of their specific expertise) identified the guidelines' key questions and developed them following the PICO format (Population, Intervention, Comparison, Outcomes). For each of the PICO questions, the systematic review of the literature was made on the most important scientific databases (Pubmed, Scopus, Embase)